Plan de negocio para la exportación de banano orgánico de la Asociación de Producción Agrícola 16 de agosto (ASOPROADAG) del cantón Balao, provincia del Guayas, al mercado europeo. - Castro Vivar, Alisson Vanessa (2022)
The present work "BUSINESS PLAN FOR THE EXPORT OF ORGANIC BANANA FROM THE ASSOCIATION OF AGRICULTURAL PRODUCTION 16 OF AUGUST (ASOPROADAG) OF THE CANTON BALAO, PROVINCE OF GUAYAS, TO THE EUROPEAN MARKET", is carried out as a contribution for the association to start exporting directly its organic banana to the European Union, since this market has a wide demand for this product. This research work is composed as follows: the first part is the literature review, where the frame of reference, theoretical framework and conceptual framework were established, which helped as support for the development of the business plan. In the second part, the research methods were established; a mixed approach was used, using quantitative, qualitative and descriptive research methods, which helped to collect information through the application of interviews, surveys and direct observation. As a third part, the results obtained were presented through tables, graphs and the respective analysis and interpretation; then the discussion was established in which an analysis of the internal and external environment of the association was made to know the current situation; the main strengths, weaknesses, opportunities and threats could be evidenced, which could be solved through the application of the business plan. A market study was also conducted to determine the unsatisfied demand in the European banana market, obtaining an unsatisfied demand of 263,486,495 boxes of bananas for the year. Through the development of the marketing plan, different strategies were designed to improve the association's image and the different means of advertising, distribution, and the price of the banana box were defined. The technical study defined the location of the offices, which will be located in the city of Machala, the storage area and the farms, which are located in Libertad del Cantón Balao in the Province of Guayas; the size of the project was also established, where it was defined that the percentage of participation in the association's market is 0.068% for the first year, and the different technical, human and material requirements that the association needs to carry out the export process were also established. Regarding the legal aspects, the necessary documentation to become an exporter was established and the steps to be able to export through ECUAPASS were described. The administrative study determined the organizational structure and the function manuals detailing the positions, functions and responsibilities of each person. Through the financial study, the total investment required by the project for its execution was determined, which has a value of $95,705.26; and, the financial evaluation was carried out, which helped determine the feasibility of the project, the NPV obtained is $ 6. 041,856.24, the IRR of 20.07%, the profit obtained is $1.80 for each dollar invested and a capital recovery period of 2 months, this represents that the project is viable, and that it is not sensitive to the increase in costs of 42% and a decrease in income of 62%. As a next step the conclusions and recommendations were presented, which were obtained from the results of the research, as another step the bibliography used for the use of the project was placed, and finally the annexes that support the study carried out. Key words: export of organic banana; agricultural production of Balao Canton; demand and supply of organic banana to the European market.